Studying chemical indicators of date seed powder and comparing it with coffee bean powder and indicating the possibility of making coffee from it (Damascus University Journal of agriculture sciences, 2022)
This research was conducted at the laboratories of the Food Sciences Department at the Faculty of Agricultural Engineering, Damascus University, during 2020-2021, to assess the possibility of  benefiting from date seed powder as a healthy alternative to coffee bean powder, by studying some chemical indicators, the content of caffeine, some mineral elements and color indices of date seed powder (Khodry) compared with coffee bean powder, and studying the effect of replacing coffee bean powder with date seed powder at different proportions (0, 4, 9, 12, 100%) on sensory properties of coffee compared to control (coffee prepared from 100% coffee bean powder). Results showed a higher content of Khodry date seed powder from moisture (2.82%) and a lower content of ash (1.27% dry weight), total sugars (5.43 g/100g dry weight), total acidity (0.329% dry weight) and pH (4.91) compared with coffee bean powder. Khodry Date seed powder sample was significantly higher in its sodium content, which reached (336.66 mg/100g, based on wet weight), while coffee bean powder sample showed a significant increase in its content of phosphor, potassium and caffeine, which reached (443.92 mg/100g, 1912.37 mg/100g, 1.04%, based on dry weight), respectively. Using date seed powder by 100%, significantly improved all sensory characteristics of coffee (color, taste, smelt, general acceptance and texture) compared with other studied samples.
Keywords: Khodry Date Seed Powder; Coffee Bean Powder; Chemical Indicators; Mineral Elements; Caffeine; Sensory Properties